Never say genius - Gutman, Dan (Gutman, Dan. Genius Files, 2012)
As their cross-country journey with their parents continues through the midwest, twins Coke and Pepsi, now thirteen, again face strange assassins at such places as the first McDonald's restaurant and Cedar Point amusement park.